PELAKSANAAN TUGAS POKOK DAN FUNGSI PENEGAK HUKUM TERPADU TERHADAP TINDAK PIDANA PEMILU - Indrapraja, Irwan S; Afida, Karania Fadillah (Universitas Muhammadiyah Ponorogo, 2024)
This writing aims to determine the extent to which gakkumdu carries out its main duties and functions carried out in the event of an election violation and the effectiveness of Gakkumdu in resolving an election violation. The statutory approach and the approach to related concepts are used in this normative juridical research. One of the methods used by the author to assist this research is data collection after that, a research stage called â€œfield researchâ€, where primary data is collected through an interview process with the subject. The author provides an overview of the provisions relating to the problem using descriptive analysis research specifications. Then further analyzed in using the regulation of legislation and releveant theories. The theory used is Deterrence which emphasizes the use of punishment as a tool to prevent future election violations. The results that the author gets state that the gradual violations that occur during elections have the potential for a criminal offense. Election crimes can be committed by election participants and the general public as voters and even by the organizers of the elections themselves. Gakkumdu is an institution authorized to enforce the law against criminal violations starting from the investigation process and the investigation process to the prosecution process and does not involve other law enforcement institutions when making decisions. Gakkumdu does not run effectively, even though it is a special institution that handles cases of alleged election crimes and has the task of handling and reducing the occurrence of election criminal violations. This study shows that Gakkumdu failed to follow the laws and regulations when handling election violations.